Alterations in the Levels of Ions in Vital Organs of Indian Major Carp, Labeo rohita Exposed to Profenofos - Nagaraju, Bantu; Ünlü, Erhan; Teka, Zenebe; Hagos, Zenebe; Referral, Mulugeta (Macedonian Journal of Ecology and Environment, 2016)
Freshwater fish take up salts from their ambient medium to compensate their loss through excretion. This obviously necessitates a high metabolic demand for the regulation between the energetic and osmoregulation in aquatic animals. Sodium, potassium and calcium are not only important for the maintenance of osmoregulation of body fluids but also for the transport of nutrients from the lumen of the digestive tract into intestinal cells and uptake of neurotransmitters in the brain. In the present study, the decrease in the levels of Na+ - K + , Ca2+ ions in the gill, muscle, liver and kidney exposed to lethal and sub lethal concentrations of profenofos indicates changes in the permeable properties of the cell membrane of these organs and of deranged Na+ - K + and Ca2+ ionic pumps due to the probable consequences of tissue damage. Disturbances in ion regulation induced by toxicants are manifested by altered ion concentrations. A number of studies have revealed that the functional properties of macromolecules are altered under pesticide stress. To gain an insight into the ion fluxes, the ions of biological significance like Na+ - K + and Ca2+ were determined in important tissues of freshwater fish, Labeo rohita.